Optimization of Succinic Acid from Fermentation Process by Using Immobiized Escherichia Coli Cells Via Anaerobic Fermentation - Nik Nor Aziati, Abdul Aziz; Mimi Sakinah, A. M. (Universiti Malaysia Pahang, 2016)
Studies on succinic acid production by using immobilized cells are essential in the optimization and development of anaerobic fermentation process while glycerol treated used as substrate. One factor at one time (OFAT) method was performed as preliminary studies for selection of parameters range and subsequently determine its optimum condition using response surface methodology (RSM). The optimum parameter combination was found at time 3.31 hour, 40 gram mass substrate (glycerol residue treated) and 15 % inoculums. Under these optimum conditions, 125.059 g/L succinic acid concentration was obtained. The succinic acid was found linearly dependent on time, mass substrates and inoculums. Multiple regression models with high R2 values were developed to correlate the succinic acid concentration as a function of time, mass substrate and inoculums. An analysis of variance (ANOVA) showed that the inoculums had slightly higher significant effect on succinic acid concentration if compared to time and mass substrates. Overall, this research showed that by using immobilized cells of Escherichia coli the production of succinic acid can be optimize and higher production of succinic acid. From this situation, the further study should be taken in genetic modification of Escherichia coli in immobilized cells to produce succinic acid as a major product to improve the fermentation process in producing the succinic acid for the future.